Respuesta :
Answer:
y = 1/6x -1
Step-by-step explanation:
Use point-slope form: y - y₁ = m (x - x₁)
y - (-2) = 1/6 (x - (-6))
y + 2 = 1/6x + 1
y = 1/6x - 1
Answer:
[tex]y=\frac{1}{6}x-1[/tex]
Step-by-step explanation:
According to,
y = mx + c
They have already given the slope of the line.
That means they've given value for m
So,
m = [tex]\frac{1}{6}[/tex]
And now we have to find the value of c ( the intercept on the y axis) using (-6,-2)
Here,
( -6 , -2 )
↑ ↑
( x , y )
Let us find the c now.
y = mx + c
[tex]-2 =\frac{1}{6} *-6+c\\-2=\frac{-6}{6} +c\\-2=-1+c\\-2+1=c\\-1=c[/tex]
Now let's write the equation of the line like this
y = mx+ c
[tex]y=\frac{1}{6}x-1[/tex]
Hope this helps you.
Let me know if you have any other questions :-)